![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: =(x^2+x-6)(x^2+x-8)
=(x+3)(x-2)(x^2+x-8)
b: =(x^2+x)^2+4(x^2+x)-12
=(x^2+x+6)(x^2+x-2)
=(x^2+x+6)(x+2)(x-1)
c: =x^4-x^3+3x^3-3x^2+8x^2-8x+12x-12
=(x-1)(x^3+3x^2+8x+12)
=(x-1)(x^3+2x^2+x^2+2x+6x+12)
=(x-1)(x+2)(x^2+x+6)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(=\left(x^2+x\right)^2+4\left(x^2+x\right)-12\)
\(=\left(x^2+x\right)^2-2\left(x^2+x\right)+6\left(x^2+x\right)-12\)
\(=\left(x^2+x\right)\left(x^2+x-2\right)+6\left(x^2+x-2\right)\)
\(=\left(x^2+x-2\right)\left(x^2+x+6\right)\)
\(=\left(x-1\right)\left(x+2\right)\left(x^2+x+6\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x^2+4x+3=x^2+x+3x+3=x(x+1)+3(x+1)=(x+1)(x+3)
b) 4x^2+4x-3=4x^2+4x+1-4=(2x+1)^2-4=(2x+1-2)(2x+1+2)=(2x-1)(2x+3)
c) x^2-x-12=x^2-4x+3x-12=x(x-4)+3(x-4)=(x-4)(x+3)
d) 4x^4+4x^2y^2-8y^4=4(x^4+x^2y^2-2y^4)=4(x^4-x^2y^2+2x^2y^2-2y^4)=4(x^2-y^2)(x^2+2y^2)=4(x-y)(x+y)(x^2+2y^2)
a) \(x^2+4x+3\)
\(=x^2+x+3x+3\)
\(=\left(x^2+x\right)+\left(3x+3\right)\)
\(=x\left(x+1\right)+3\left(x+1\right)\)
\(=\left(x+1\right)\left(x+3\right)\)
c) \(x^2-x-12\)
\(=x^2-4x+3x-12\)
\(=\left(x^2-4x\right)+\left(3x-12\right)\)
\(=x\left(x-4\right)+3\left(x-4\right)\)
\(=\left(x-4\right)\left(x+3\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x2 + 4x + 3
= x2 + 3x + x +3
= ( x2 + 3 ) + ( x + 3 )
= x ( x + 3 ) + ( x + 3 )
= ( x + 3 ) ( x + 1 )
b) 4x2 - 4x - 3
= 4x2 + 2x - 6x - 3
= ( 4x2 + 2x ) - ( 6x + 3 )
= 2x ( 2x + 1 ) - 3 ( 2x + 1 )
= ( 2x + 1 )( 2x - 3 )
c) x2 - x - 12
= x2 + 3x - 4x - 12
= ( x2 + 3x ) - ( 4x + 12 )
= x ( x + 3 ) - 4 ( x + 3 )
= ( x + 3 ) ( x - 4 )
d) 4x4 - 4x2y2 - 8y4
= 4 ( x4 - x2y2 - 2y4 )
Hk tốt
\(y^2+4y=12\Leftrightarrow\left(y+2\right)^2=4+12=4^2\)
\(\orbr{\begin{cases}y=0\left(1\right)\\y=-4\left(2\right)\end{cases}}\)
\(\left(1\right)\Rightarrow\orbr{\begin{cases}x=0\\x=-1\end{cases}}\)\(\left(2\right)\Leftrightarrow\left(x+\frac{1}{2}\right)^2=\frac{1}{4}-4< 0\left(vo.nghiem\right)\)
Nhầm: \(\orbr{\begin{cases}y+2=4\left(1\right)\\y+2=-4\left(vo.nghiem\right)\end{cases}}\)
\(\left(1\right)\Leftrightarrow\left(x+\frac{1}{2}\right)^2=2+\frac{1}{4}=\frac{9}{4}\Rightarrow x=\orbr{\begin{cases}-\frac{1}{2}+\frac{3}{2}=1\\-\frac{1}{2}-\frac{3}{2}=-2\end{cases}}\)